ANALISIS MISKONSEPSI PADA PEMBELAJARAN BAHASA INDONESIA KETERAMPILAN MENULIS DI SEKOLAH DASAR - Inangi Meisella, Gayan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the types of misconceptions that occur in the teaching of Indonesian writing skills in elementary schools through a literature review approach. Misconceptions are understood as incorrect understandings of linguistic concepts or rules, which result in low-quality student writing. The method used is descriptive qualitative, with data collected through a review of relevant scholarly articles. The findings show that misconceptions in writing occur in aspects such as text structure, spelling, punctuation, coherence, and word choice. These findings highlight the importance of teaching strategies that can identify and address misconceptions from an early stage.